THE EFFECT OF WEBSITE QUALITY AND TRUST ON CUSTOMER LOYALTY - Rahmi Afrelia; Lia Hidayah; Ayu Setianingsih; Ade Irma Hariani Hasibuan (Journal of Islamic Economic Scholar, 2020)
This study aims to determine the effect of website quality and trust on Shoppee customer loyalty. This research uses survey method, where the research instrument uses a questionnaire that is distributed online using WhatssApp media. The population in this study are students of UIN Sunan Kalijaga Yogyakarta who have shopped or have subscribed to Shoppee. The sample in this study were 100 respondents obtained based on purposive sampling technique. This study uses a validity and reliability test using analytical techniques using the IBM SPSS Statistics version 16.0. The results found that: (1) Website Quality has a positive effect on Shoppee customer loyalty; (2) Trust has a positive effect on Shoppee customer loyalty.